(untitled) (Panacea Journal of Medical Sciences, 2024)
Introduction: Fine needle aspiration cytology (FNAC) is widely accepted as a primary method for the diagnosis of thyroid lesions. An alternative to FNAC is fine-needle sampling without aspiration (FNNAC). FNAC is easy to perform, quickly and has a high degree of sensitivity and specificity and avoid unnecessary surgery. Hence the present study was performed to study the diagnostic accuracy of FNNAC with FNAC technique in solid tumors. Materials and Methods: An observational study was carried out on 325 patients with swellings in the breast, thyroid, and soft tissues and enlarged lymph nodes in the Department of surgical oncology, Regional Cancer Centre, Government Coimbatore Medical college hospital, Coimbatore, India. A single pathologist was responsible for all cytological and histological reports. Slides of both approaches were analysed and compared using Mair et al grading methodology, which depends on five factors. The number of smears with superior quality and diagnostic accuracy is compared and analysed statistically using the ’z’ test for two proportions. Results: FNNAC produced better smears with less haemorrhage in vascular organs like the thyroid. FNAC performed better in breast fibrous lesions such as fibroadenoma and phyllodes tumour. For malignant lumps of breast and lymph nodes, FNAC yields better material than FNNAC. Conclusion: The current research shows that FNNAC is the superior approach for highly vascular organs such as the thyroid because it yields high-quality smears with less blood admixtures. Although FNAC smears were more often diagnostic, they typically yielded acceptable rather than excellent grade smears.